Develop a Video Tutorial on Basic Sepak Badek Techniques in Sepak Takraw for Physical Education Students in the 2021/2022 Academic Year - I Ketut Semarayasa; Ketut Karin Preayani (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Objective. The rapid advancement of technology has led to significant innovations in various fields, including education. Educators are expected to leverage these technological developments to design new and effective learning strategies for their students. This study focuses on the development of video tutorial-based learning media that employs the ADDIE model to teach basic football sila techniques in the context of the sepak takraw game. This learning product is specifically designed for students enrolled in the Penjaskesrek study program. Material and Methods. The ADDIE development model is a well-known instructional design approach that consists of five key stages; analysis, design, development, implementation, and evaluation. For the purpose of this research, a score scale questionnaire was utilized as the data collection instrument. Result. According to the research findings, the teaching materials were well-received in terms of their content, with a 93.33% rating. The learning media element was also highly rated, with a score of 93.33%. Similarly, the learning design part received a very good rating of 96.25%. The field practitioner aspect of the materials also received a good rating of 92.00%. During individual product trials, the criteria received a rating of 91.10%, while small-group product trials received a rating of 94.66%. Conclusion. The study concluded that the instructional materials for learning basic sepak takraw techniques, which were based on video tutorials, were found to be both feasible and effective for Penjaskesrek study program students. The research indicates that these materials can be incorporated into the curriculum to enhance the learning experience of students in the fields of physical education, sports, and health. Overall, the findings suggest that utilizing video tutorials as a form of instructional media can be a valuable tool in facilitating the acquisition of fundamental skills in sepak takraw.